Efek Spray Limbah Tembakau (Nicotiana tabacum L.) terhadap Kematian Nyamuk Aedes aegypti - Fennyta Fika Fiyanza; Widya Hary Cahyati; Irwan Budiono (Dian Nuswantoro Semarang, 2017)
Aedes aegypti is the main vector of dengue virus carriers with Ae. Albopictus. Using chemical insecticide are popular in society as vector control will impact resistance in mosquito. Tobacco waste was a plant that contains alkaloid, nikotine, and flavonoid which its function as insecticides. The purpose of this research was to determine the lethal effect test of tobacco waste insecticides. This research was true experimental research, by post test only with control group design in six variations of the extract concentration 5 %, 9 %, 15 %, 24 %, 40 %, and 64 % with four times repetitions. The results of Kruskal Wallis test shows that there are differences average of mortality Aedes aegypti at various concentrations of cambodia extract, which significance or probability value is 0,001. From probit analysis test, LC50 is found in level 13,627 % and LC90 in level 76,996 %. The researcher suggested there should be a further research what is the active ingredients contained in the new tobacco waste and the dried tobacco waste because it exposured to sunlight.Keywords: Aedes aegypti, insecticide, tobacco waste, extract